المؤشرات السياحية في دول المينا حسب تقرير التنافسية العالمي 2019 - عريس مختار; العرابي عبد الغني (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2022)
في هذه الدراسة، قمنا باقتراح بعض الإجراءات الضرورية لإنعاش قطاع السياحة. حيث توصلنا إلى أن قطاع السياحة في دول شمال إفريقيا والشرق الأوسط، لازال في مؤخرة الأولويات، في سياسات أغلب الدول العربية. والتي تعتبر بعضها من بين الدول التي تحتل المراتب الأولى في الترتيب العالمي، في بعض المؤشرات، كما تحتل المراتب الأخيرة في مؤشرات أخرى، في قطاع السياحة. الذي تمحورت حوله هذه الدراسة، من خلال إبراز محددات تنافسية السياحة والسفر، وفق تقرير التنافسية العالمي 2019. لدول الشرق الأوسط وشمال إفريقيا (المينا). وقد اعتمدنا على المنهج الاستنباطي، من خلال الوصف والتحليل. In this study, we have proposed some necessary actions to revive the tourism sector. We found that the tourism sector in the countries of North Africa and the Middle East remains at the top of the priorities in the policies of most Arab countries. Some of them are among the countries that occupy the first places in the world ranking, in some indicators, and also occupy the last places in other indicators, in the tourism sector. This study focused on highlighting the determinants of Tourism and travel competitiveness, according to the Global Competitiveness Report 2019. For the Middle East and North Africa (MENA) countries. We have relied on the deductive method, through description and analysis.